2017
DOI: 10.1016/j.neuropsychologia.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Primary motor cortex functionally contributes to language comprehension: An online rTMS study

Abstract: ABSTRACT:Among various questions pertinent to grounding human cognitive functions in a neurobiological substrate, the association between language and motor brain structures is a particularly debated one in neuroscience and psychology. While many studies support a broadly distributed model of language and semantics grounded, among other things, in the general modality-specific systems, theories disagree as to whether motor and sensory cortex activity observed during language processing is functional or epiphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 77 publications
10
113
1
2
Order By: Relevance
“…Magnetoencephalography (MEG) studies further show that these responses occurred earlier than the typical semantic processing window for words (Mollo, Pulvermüller, & Hauk, 2016). This supports the hypothesis that sensorimotor mapping is not merely from post-comprehension processes (see also Vukovic, Feurra, Shpektor, Myachykov & Shtyrov, 2017, for evidence that repetitive Transcranial Magnetic Stimulation (rTMS) to motor cortex impairs retrieval of actions verbs). Rather, these sensorimotor mappings may in fact be a fundamental neural mechanism of verb-semantic processing.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Magnetoencephalography (MEG) studies further show that these responses occurred earlier than the typical semantic processing window for words (Mollo, Pulvermüller, & Hauk, 2016). This supports the hypothesis that sensorimotor mapping is not merely from post-comprehension processes (see also Vukovic, Feurra, Shpektor, Myachykov & Shtyrov, 2017, for evidence that repetitive Transcranial Magnetic Stimulation (rTMS) to motor cortex impairs retrieval of actions verbs). Rather, these sensorimotor mappings may in fact be a fundamental neural mechanism of verb-semantic processing.…”
Section: Introductionsupporting
confidence: 79%
“…The existence of bimodal units responding to both visual depictions of actions and verbs describing actions (discussed further below) provides additional evidence consistent with this hypothesis. Also consistent with this is the fact that transcranial magnetic stimulation to motor areas interferes with action-verb processing (Vukovic, et al, 2017). …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Studies using fMRI, TMS, MEG, and the EEG mu rhythm have found activation of the motor system when adults process (hear or read) verbs or phrases about actions (Di Cesare, Errante, Marchi, & Cuccio, ; Egorova, Shtyrov, & Pulvermüller, ; Hauk, Johnsurde, & Pulvermüller, ; Moreno et al, ; Moreno, de Vega, & León, ) or while decoding degraded speech sounds (d'Ausilio, Bufalari, Salmas, & Fadiga, ). Indeed, there is evidence that the motor system is functionally linked to representing action‐related language (Vukovic, Feurra, Shpektor, Myachykov, & Shtyrov, ), and some studies have also found left‐hemisphere specificity for the action‐language link (e.g., Pulvermüller, Hauk, Nikulin, & Ilmoniemi, ). Other TMS studies show motor areas are involved during the hearing of speech sounds or phonemes with no clear meaning, thus suggesting a phonological resonance within the motor cortex (d'Ausilio et al, ; Fadiga, Craighero, Buccino, & Rizzolatti, ; Roy, Craighero, Fabri‐Destro, & Fadiga, ).…”
Section: Mirroring and Communicationmentioning
confidence: 99%
“…Pulvermüller, Hauk, Nikulin, and Ilmoniemi () found that priming the respective effector representation area of primary motor cortex (M1) using single‐pulse transcranial magnetic stimulation (TMS) decreased reaction times for responding to words describing actions performed by the stimulated effector. Vukovic, Feurra, Shpektor, Myachykov, and Shtyrov () found that online repetitive TMS to the motor cortex slowed reaction times to action words, while leaving reactions to abstract words unaffected. These experiments bolster the view that sensorimotor systems in the brain are not only activated by language comprehension but play active roles in understanding.…”
Section: Introductionmentioning
confidence: 99%